Design of Material Needs Profile in Reading Learning Textbooks based Riau Malay Folklore - Asnawi, Asnawi; Muhkhlis, Muhammad; Rusmani, Ayu; Zulfa, Mukminati (Universitas Pendidikan Mandalika, 2024)
This study aims to identify the needs for the content of textbooks for learning to read which contain texts from Riau Malay folklore. The approach used in this research was qualitative with a descriptive method. The data collection techniques were questionnaires and interviews. Based on an analysis of the content aspects of textbooks for learning to read, there are several conclusions. First, students want textbook material that includes depth of material and examples of material to facilitate learning; second, students want the accuracy of textbook material which includes examples of material so that it is easy to understand; third, students want up-to-date textbook material and in accordance with the psychological development of students; fourth, students want noble values in textbooks to benefit their readers; and fifth, students want to use cliche language in the content of Riau Malay folklore which is taught in textbooks, so that they can increase their knowledge of the clichÃ© language used in Riau Malay folklore. In addition, students also want the text of Riau Malay folklore in textbooks to add new knowledge about this folklore.